natural resource management and legal consequences for the environment from the perspective of international environmental law - Tethool, Adjeng; Kainama, Marthinus (Faculty of Law, Universitas Jambi, 2023)
Inappropriate management of natural resources can cause international problems such as air pollution. One of the pollution referred to is the forest fires that have occurred in Indonesia because they are not in line with the principles of international environmental law, one of which is the principle of sic utere tue ut alienum non leades where the state is prohibited from permitting and or carrying out activities that are detrimental to other countries which give rise to legal consequences for a country. This research tries to analyze the actions to prevent air pollution and the legal consequences of managing natural resources that pollute the air environment based on international environmental law. The method used is normative research. The results of the study show that the management of natural resources that is not in accordance with the principles of international law causes air pollution which has a negative impact on the state, causing state responsibility as stipulated in Principle 16 of the 1992 Rio Declaration which states that polluting countries must pay the costs incurred. stipulated by the competent authority for all losses incurred as a result of environmental damage by the actions taken.